Debt sustainability in Germany: empirical evidence for federal states. (6th April 2011) - Fincke, Bettina; Greiner, Alfred
This paper studies whether the public debt policies of former West German states from 1975 until 2006 were sustainable. We test if the primary surplus relative to GDP is a positive function of the public debt to GDP ratio where we allow for time-varying reaction coefficients by resorting to penalised spline estimation. We also perform stationarity tests with respect to the real budget deficit to gain additional insights. Our analysis suggests that two groups of states can be distinguished, one with states that seem to pursue sustainable debt policies. However, with one exception, even those states are characterised by rising debt to GDP ratios, which is not compatible with sustainability in the long run. For the other group, sustainability can be stated only at a low-significance level or does not seem to be given at all. Thus, all states in the second group should put much more emphasis on stabilising debt.